CO2 to CO Electroreduction, Electrocatalytic H2 Evolution, and Catalytic Degradation of Organic Dyes Using a Co(II) meso-Tetraarylporphyrin - Guergueb, Mouhieddinne; Loiseau, Frédérique; Molton, Florian; Nasri, Habib; Klein, Axel (Molecules (Basel, Switzerland), 2022)
The meso-tetrakis(4-(trifluoromethyl)phenyl)porphyrinato cobalt(II) complex [Co(TMFPP)] was synthesised in 93% yield. The compound was studied by 1H NMR, UV-visible absorption, and photoluminescence spectroscopy. The optical band gap Eg was calculated to 2.15 eV using the Tauc plot method and a semiconducting character is suggested. Cyclic voltammetry showed two fully reversible reduction waves at E1/2 = −0.91 V and E1/2 = −2.05 V vs. SCE and reversible oxidations at 0.30 V and 0.98 V representing both metal-centred (Co(0)/Co(I)/Co(II)/Co(III)) and porphyrin-centred (Por2−/Por−) processes. [Co(TMFPP)] is a very active catalyst for the electrochemical formation of H2 from DMF/acetic acid, with a Faradaic Efficiency (FE) of 85%, and also catalysed the reduction of CO2 to CO with a FE of 90%. Moreover, the two triarylmethane dyes crystal violet and malachite green were decomposed using H2O2 and [Co(TMFPP)] as catalyst with an efficiency of more than 85% in one batch.